Procalcitonin measurements and non-invasive mechanical ventilation in acute exacerbation of COPD: an appropriate new tool? - Esquinas, Antonio M. (International Journal of Research in Medical Sciences, 2017)
Hospitalization of acute exacerbations of chronic obstructive pulmonary disease (Ae-COPD) is a common health care problem. In last decades, non-invasive mechanical ventilation (NIV) is a key cornerstone therapeutic element that have shown influence positively short and long term outcomes in Ae-COPD. Recently, incorporation of new biomarkers as procalcitonin (PCT) to predict requirement of NIV in Ae-COPD is an attractive tool to guide a proper making decision regarding indication of NIV is scarce.